Effects of typical artificial reefs on hydrodynamic characteristics and carbon sequestration potential in the offshore of Juehua Island, Bohai Sea - Shu, Anping; Zhang, Ziru; Wang, Le; Sun, Tao; Yang, Wei; Zhu, Jiapin; Qin, Jiping; Zhu, Fuyang (Frontiers in Environmental Science, 2022)
The ocean system provides abundant food resources and suitable habitats for numerous animal and plant species. However, ecological health of the ocean system has deteriorated due to intensified human activities over the past decades. To mitigate negative effects, more research efforts are paid to marine ecological restoration programs at national and regional scales. As an effective method, artificial reefs were found to have an important role in restoring ecological system by producing complex flow patterns and attracting more species to settle down. This study aims to select the offshore ground of JueHua island in the BoHai sea as an artificial-reef-driven ecological restoration site, to tentatively estimate effects of square and M-shaped artificial reefs on localised flow fields, biomass production, and offshore carbon sink capacity. In so doing, a relatively complete carbon sink measurement system is accordingly proposed. Our results indicate that both temporal and spatial distribution of nutrients and habitat environments are dependent on flow characteristics modified by artificial reefs in different size, shape and configuration. Future ecological restoration measures in offshore waters should take carbon sink and relevant influencing factors into consideration.